Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper examines the impact of key structural fiscal reforms on growth and other macro variables in Thailand. The study simulates the impact of: a public infrastructure push; labor market policies, including an increase in the pensionable age and in provision of childcare services; and a change in the composition of taxes from income taxes to value added tax to shed light on the desired composition of additional taxes to be levied in the longer term. The results indicate that structural reforms enabling higher infrastructure investment, stronger labor participation, and more efficient taxation can raise growth significantly and contribute to addressing domestic and external imbalances.